Methodological approach to the study of dynamics of specific concentration of cell wall antigens per cell of Bacillus species and examples of its application - Kiseleva Elena Pavlovna; Mikhailopulo Konstantin Igorevich; Ladutska Alena Ivanovna; Novik Galina Ivanovna (The EuroBiotech Journal, 2017)
Background: Nonpathogenic Bacillus strains are used in biotechnology, and pathogenic Bacillus strains are cause of food borne disease. It explains the relevance of the methods of detection and quantification of whole cell and cell components of these bacteria. Aims: Development of methodological approach for investigation of dynamics of specific concentration of cell wall antigens per cell of bacilli without solubilization of cell wall during sample preparation; using of the approach with 6 strains of bacilli as an example. Method: ELISA. Results: Methodological approach for investigation of dynamics of specific concentration of bacilli cell wall antigens has been developed. The distinctive features of the approach are rabbit polyclonal antibodies to genera-specific antigens of bacilli as key reagent and lack of need for solubilization of cell wall during sample preparation. It was shown using 6 strains of Bacilli as an example that specific concentration of cell wall antigens per cell vary according to bacillus strain, stage of culture growth and media composition. The data will find an application in biotechnology of clinical diagnostics and test-systems for food control including detection of whole bacillus cells.